THE IMPORTANCE OF 5G NETWORK FOR TRAFFIC AND AUTOMOTIVE INDUSTRY WITHIN THE SCOPE OF INTERNET OF THINGS (IoT) - Jelenković, Sanja (Ekonomija - teorija i praksa, 2022)
This paper is based on research into the representation of modern Information Technology using the 5G network, which gives us great technological opportunities in the automotive industry. The Internet of Things (IoT) gives us great opportunities for smart cities, namely, smart streets that are driven by technologically advanced new generation cars equipped with smart vehicle control devices suitable for all traffic conditions, ranging from heavy traffic jams to various weather conditions. 5G is literally driving innovation, as 5G is an important technology for the automotive industry. With 5G we get better coverage, higher capacity, lower latencies (wait times) and much higher data rates. This will allow your car not only to use Spotifi (a free music streaming and playback app) for the long haul, but will also improve the ride itself, gathering information from other cars, pedestrians, traffic lights and even the road itself. It is run by a cloud-based computer (thousands of computers in particular) that calculates and adjusts our vehicle every millisecond (current situation). The self-contained "intelligence" of our car from our own computer will be present as a backup in case we lose our internet connection or play an ancillary role in managing the vehicle. Even without the internet, 5G communication between cars and cars, roads and pedestrians would play an important role in safely switching from A to B.